The Impact of Sleep Quality on the Menstrual Cycle of Teenage Girls at SMAN 1 Tenggarong, East Kalimantan - Mardiana, Mardiana; Mawarni, Irda; Rahman, Ferry Fadzlul (Journal of Health Management Research, 2022)
Background: An abnormal menstrual cycle is one of the early indicators of reproductive health problems in adolescent girls. One of the risk factors for the occurrence of abnormal menstrual cycles is poor sleep quality. Aims: to determine the relationship between sleep quality and menstrual cycle in adolescent girls at SMA Negeri 1 Tenggarong. Methods: This research used quantitative research with a cross-sectional design. The population was adolescent girls in SMAN 1 Tengarong as many as 350 people. The sample size was 187 people using Stratified Random Sampling. The instrument used the Pittsburgh Sleep Quality Index (PSQI) Questionnaire and the Menstrual Cycle Questionnaire. The statistical test used the Contingency Coefficient test with = 5%. Results: Based on the results of the research, it was found that the contingency coefficient test results were 0.003 < 0.05. It means that there was a relationship between sleep quality and menstrual cycle in adolescent girls of SMA Negeri 1 Tenggarong. Conclusion: Sleep quality has a relationship with the menstrual cycle in adolescent girls. The results of the research can be used as reference material, evaluation, and consideration in promotive and preventive efforts to improve reproductive health in adolescent girls.